Efeito da distribuição do tamanho das partículas abrasivas sobre as taxas e modos de desgaste para o ensaio de microabrasão - Gómez, Víctor Alfonso Osma (2014)
In this work, the particle size distribution of two silicon carbide (SiC) powders was initially analyzed, indicating a normal (Gaussian) distribution for both powders, with average particle size on the order of 2 m in one case and 6 m in the other. The two original powders were then mixed with different mass fractions, providing a new series of SiC powders that were used in micro-scale abrasive tests with fixed-ball configuration. The characterization of these new powders showed larger widths for those with a high percentage of small abrasive (2,11 μm) retaining the Gaussian appearance of the original. In contrast to powders with a high amount of the larger abrasive (6,57 μm), the curves obtained has a slight tendency bimodal, but showed larger widths also.The wear tests were conducted on AISI 1020 carbon steel for two differents conditions of normal load and the results were analyzed in terms of wear rate as well as wear mode (“rolling abrasion” or “grooving abrasion”). Results have indicated that the mass fraction of the original powders has a significant effect on the wear modes observed and that the wear rate does not follow a direct relationship with the mass fraction of the powder with larger average particle size. Furthermore, the analysis of the severity of contact determined that this decrease during the tests conduced with constant normal load. This phenomenon is associated with increased area of the crater wear that produces a decrease in contact pressure. Thus an increase in particle rolling should be expected, favoring the observation of multiple indentations along grooves formed previously. This was confirmed by scanning electron micrographs of the samples after micro-abrasion tests.